2013
DOI: 10.1098/rsbl.2012.0888
|View full text |Cite
|
Sign up to set email alerts
|

Nestling erythrocyte resistance to oxidative stress predicts fledging success but not local recruitment in a wild bird

Abstract: Stressful conditions experienced by individuals during their early development have long-term consequences on various life-history traits such as survival until first reproduction. Oxidative stress has been shown to affect various fitness-related traits and to influence key evolutionary trade-offs but whether an individual's ability to resist oxidative stress in early life affects its survival has rarely been tested. In the present study, we used four years of data obtained from a free-living great tit populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…The transition from nestling to fledging is marked by high mortality in free-living birds. Fledglings in better condition are more likely to survive to adulthood [70]. Therefore, by investing in parental care and increasing nestling quality, males living in stressful environments could maximize the survival of their nestlings and, hence, their fitness.…”
Section: Resultsmentioning
confidence: 99%
“…The transition from nestling to fledging is marked by high mortality in free-living birds. Fledglings in better condition are more likely to survive to adulthood [70]. Therefore, by investing in parental care and increasing nestling quality, males living in stressful environments could maximize the survival of their nestlings and, hence, their fitness.…”
Section: Resultsmentioning
confidence: 99%
“…Thus oxidative damage caused by the increased metabolism could limit mass gain before fledging, which is correlated with fledging success (Losdat et al, 2013). Antioxidants could therefore play an important role during the nestling phase.…”
Section: Research Articlementioning
confidence: 99%
“…The opposite effects of these two important environmental factors (food availability (this study) vs. parasitism (De Coster et al 2012)) on the oxidative status of male and female nestlings highlights the different sensitivities of the two sexes to environmental factors, with subsequent consequences on physiological mediators of variation in fitness (Noguera et al 2012;Losdat et al 2013). The higher sensitivity of female nestlings to food limitation early in life suggests that females might pay a higher price for the increasing mismatch between food availability and demand due to climate change observed in many bird species (Thomas et al 2001;Visser et al 2003) Generally, we found no strong relationships between the measured markers of oxidative damage or protection and nestling growth, fledging size or mass.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant capacity is positively, while oxidative damage negatively related to survival (Freeman-Gallant et al 2011;Saino et al 2011). Furthermore recent studies showed that the ability of nestlings to cope with oxidative stress predicts their fledging success (Losdat et al 2013) and their recruitment probability (Noguera et al 2012), highlighting that an efficient antioxidant protection is beneficial from the first stages of life. However, investment in such an efficient oxidative protection is likely associated with costs.…”
Section: Introductionmentioning
confidence: 99%